Dampak Perubahan Nilai Tukar terhadap Indeks Harga Konsumen Bahan Makanan di Indonesia - Suarsih, Siti; Achsani, Noer Azham; Nuryartono, Nunung (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
The fluctuation in exchange rate Indonesia may have an impact on the price of imported goods both consumer goods (finished goods) and raw materials. The aim of this study is to analyze the impact of exchange rate changes on the Consumer Price Index (CPI) of foods categories and analyze the role of the exchange rate in explaining fluctuations in the CPI of food category in Indonesia. Econometric analysis using vector error correction model, indicates that the greatest degree of pass-through occurs in the consumer price index groups of milk and eggs. Contributions of exchange rate as the result of decomposition of forecasting error variance is largest in the meat category.